Strategic scripts for the twenty-first century - Freedman, Lawrence (UK Data Service, 2014)
Strategic Scripts for the Twenty-First Century involves three linked strands, each geared to developing the idea of 'strategic scripts' as a means of addressing a broad range of security issues. The first will explore the extent to which strategies can be presented as scripts, rather than as plans, and how this might be a useful device for translating research into policy in areas of actual or potential conflict. This will consider the distinctive features of this research compared with other areas of public policy. The second and third strands will apply the concept of strategic scripts to two contrasting areas of security policy. One will examine the interaction between the current push for substantial nuclear disarmament, even up to full abolition, and established theories of deterrence, and take in the 2010 Nuclear non-Proliferation Treaty Review Conference. The other will contrast the strategic scripts of al Qaeda and other radical Islamist groups, from 1998 to 2011, and compare them with those developed within two other radical traditions, Marxism within industrialised countries and the secular, anti-colonial third world movements which came to the fore in the 1950s and 1960s. The project will involve a post-doctoral researcher and two postgraduate research students.